ولاية العلاج في الفقه الإسلامي - خرخاش, عصام (جامعة الوادي University of Eloued, 2017)
فإنّ من نعم الله تعالى على الإنسان أن جعل له عقلا يدرك به المصالح والمفاسد ويدّبر به شؤونه، وأقام الولاية على النفس والمال على الصغار ومن أصيب في عقله بجنون أو سفه أو عته أو غيبوبة أو مرض يمنعه من مباشرة مصالحه، لتحقيق المصلحة المعتبرة شرعا. ولما كان الطب وضع لجلب مصالح السلامة والعافية، ولدرء مفاسد المعاطب والأسقام، أجاز الشرع التداوي ومباشرته، من المريض أصالة، أو ممن ينوبه استثناءً. Abstract: Al-Shara established the tutelage upon self and money on the young and those who were mentally ill , Dementia, ribald, coma or disease that prevented him from exercising his interests. As the medecine is the mode of bringing the interests of safety and wellness, The Sharia has permitted medication by the patient's authenticity, or by the sponsor as exception.
The Tutelage Of Treatment In Islamic Jurisprudence
Keywords: الطب- العلاج- الولاية- الفقه- المصلحة; medecine – medication – tutelage - jurisprudence – interest